THE EFFECT OF INVESTMENT ON ECONMIC GROWTH WITH EXPORTS AS A MODERATING VARIABLE - Arie Fitria; Regina Regina; Eva Yuniarti Utami; Arifia Nurriqli; Alya Elita Sijoen (ITB AAS Indonesia Surakarta, 2024)
This research is quantitative research with an exploratory approach, namely an approach that uses a number of previous studies as the main reference for finding elements of Novelty and Research Gap in this article. The data used in this research is secondary data that researchers obtained from the annual Central Statistics Agency reports from 2014-2024. The data used was analyzed using the smart PLS 4.0 analysis tool with the hypothesis formulation below. The result in this article show the investment variable has a positive relationship and a significant influence on economic growth. This is because the P-Values value is positive and is below the 0.05 significance level, namely 0.003. This is because large investments can improve all lines that can boost growth, both in terms of industry, education, health, and so on. Apart from that, in the second row of the third table, the Path Coefficient above shows that the Export variable can moderate the influence of the Investment variable on Economic Growth due to the same thing, namely the direction of the positive relationship of P-Values and is below the significance level of 0.05, namely 0.000, which is more significant than the direct test of 0.003. . In this way the first and second hypotheses in the research can be accepted and proven. Keywords: Investment, Econmic Growth, Exports